Alternative energy a true book - Petersen, Christine (New York Children's Press, 2004)
Discusses various forms of energy derived from renewable resources, such as wind power, solar power, water power, geothermal energy, and biofuels
Includes bibliographical references and index
Hurg
5 18
Keywords: Power resources; Renewable energy sources